Correlation analysis of serum levels of H19 and CRP levels and ulcerative colitis: Clinical significances of H19 and CRP levels in UC - Wang, Aihua; Jiang, Yongkang (Journal of Medical Biochemistry, 2022)
Background: To elucidate clinical applications of detecting serum levels of H19 and CRP in predicting the severity of ulcerative colitis (UC). Methods: Two hundred UC patients were recruited, and classified to mild/moderate group and severe group according to the Truelove-Witts grading system. Serum levels of H19 and CRP in UC patients were detected by turbidimetric inhibition immuno assay and qRT-PCR. Differences in serum levels of H19 and CRP between mild/moderate group and severe group were analyzed. By plotting ROC curves, the diagnostic potentials of H19 and CRP in UC were evaluated. Kappa conformance test was conducted to validate the conformance of detecting serum levels of H19 and CRP to clinical diagnosis of UC. Results: Serum levels of H19 and CRP were higher in UC patients of severe group than those of mild/moderate group. Their levels were both positively correlated to the severity of UC. High sensitivity (83.3%) and specificity (80.0%), as well as the maximum Youden index (0.633) were obtained at the cut-off value for H19 level of 2.755, and AUC was 0.8835. Meanwhile, Kappa coefficient (κ) was 0.760 at the cut-off value for H19 level of 2.755, showing a high conformance to clinical diagnosis of UC. In addition, acceptable sensitivity (68.49%) and high specificity (85.83%), as well as the maximum Youden index (0.543) were obtained at the cut-off value for CRP level of 6.390 mg/L, and AUC was 0.8018. κ was 0.435, showing an acceptable conformance to clinical diagnosis of UC based on serum level of CRP.Conclusion: Serum levels of H19 and CRP increase with the deterioration of UC. Detecting their serum levels has a consistent result to clinical diagnosis of UC, with a superior performance of H19 than that of CRP.
Keywords: Ulcerative colitis; H19; CRP